1955
DOI: 10.1161/01.cir.11.4.517
|View full text |Cite
|
Sign up to set email alerts
|

Certain Clinical States and Pathologic Changes Associated with Deeply Inverted T Waves in the Precordial Electrocardiogram

Abstract: A correlation of the clinical and electrocardiographic findings was undertaken in 110 cases which had in common the presence of deeply inverted T waves in central terminal leads centered about position 3 on the precordium. The results of this study are reviewed. A summary is presented of changes encountered at the time of necropsy in nine cases in which electrocardiographic changes of similar type had been recorded. These observations are integrated with concepts derived from the dipole theory. The total evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1957
1957
2011
2011

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…The adult patients were from both the ward and private niedical and surgical services during a period of approximately 4 months. Although usually the records were taken for specific clinical indications, some represented routine preoperative electrocardiograins in the elderly age group.…”
Section: Methodsmentioning
confidence: 99%
“…The adult patients were from both the ward and private niedical and surgical services during a period of approximately 4 months. Although usually the records were taken for specific clinical indications, some represented routine preoperative electrocardiograins in the elderly age group.…”
Section: Methodsmentioning
confidence: 99%
“…1). Three patients had post-operative E.C.G.s which indicated probable fresh infarction; in two there was widespread deep symmetrical T-wave inversion of a type known to be associated with subendocardial infarction (Pruitt et al, 1955;Garcia-Palmieri et al, 1956) (Fig. 2), and in the other Age did not appear to be an important factor in determining risk.…”
Section: Methodsmentioning
confidence: 95%
“…1-7 In addition, such an ECG presentation has been documented along with a total occlusion of the first diagonal branch, in which case it represents subendocardial ischemia of the border zone surrounding the area of mid-anterior transmural ischemia; it is recorded in leads V4-V5 and sometimes in V3 along with STE in leads aVL and V2 and sometimes in I. [2][3][4][5]8 This ECG pattern has been presented by Pruitt et al 9 whereas, later on, De Servi et al 10 recorded it following ergometrine maleateinduced subtotal LADA occlusion. Sclarovsky et al 2 showed that 86% of the patients with precordial STD and positive T wave had a significant LADA or diagonal branch stenosis.…”
Section: Commentmentioning
confidence: 96%